A Bornean Longhouse in Kahayan and Kapuas River Basin: The Process of Metamorphosis Architecture - Tari Budayanti Usop; T. Yoyok Wahyu Subroto; Sudaryono Sudaryono; Muhammad Sany Roychansyah (International Journal of Disabilities and Social Inclusion, 2021)
This paper analyzes the process of changing living space in the Dayak tribes in Central Kalimantan, which is a complex phenomenon. The process of spatial discussion in Dayak settlements is useful in the planning and design process relating to housing and settlements, among others concerning environmental aspects, relocation, resettlement, urban renewal, and preserving local wisdom. This research is trying to develop the concept of change in living space that starts from a Dayak community value at the level of transition by using local material as a reference. The Dayak tribes in Central Kalimantan as the object of this study, specifically those in the large and small watersheds of Central Kalimantan as a reference, and field research as a research method. Asking research questions that arise is like asking whether the spatial discussion process is carried out on Dayak tribes in Central Kalimantan. The steps undertaken to answer the research questions are: first, finding the initial process of the Dayak concept of settling; second, to find the concept of changing space from non-permanent (nomadic) to semi-permanent (settled) and settlement. The results of this study contributed to the development of a revised architectural methamorphosis theory, such as questioning the settlement process of the evolving of Dayak tribes.